(untitled) (Superficies y Vacío, 2012)
This work presents a study about the evolution of titanium oxide particles synthesized with glow discharges of water and Tetra Titanium Propoxide (TTP). The syntheses involved sequential changes of TTP from solid, liquid and vapor phases under resistive glow discharges at 13.56 MHz, 0.5-0.8 mbar and 100 W with reaction times between 60 and 240 min. The reaction of TTP and water between the electrodes originated titanium oxide powder composed of white particles with diameter between 106 and 695 nm and different geometries depending on the time of synthesis. These materials may have environmental applications in the sorption of toxic contaminants.